ORTHOGONALIZATION BY GAUSS ELIMINATION WITH ITS APLICATIONS - (NIM: 20107031), MARHAYATI
Computation in the process of Gram-Schmidt Orthogonalization is complicated and costly. This project will discuss about Orthogonalization Gaussian Elimination and its aplications. This algorithm are shorter and simple. We also using orthogonalization by Gaussian Elimination to determine the QR decomposition, least squares problem, and orthogonal basis extension.